2021
DOI: 10.1039/d0bm01604g
|View full text |Cite
|
Sign up to set email alerts
|

Polarization behavior of bone marrow-derived macrophages on charged P(VDF-TrFE) coatings

Abstract: The immune response of bone implants is closely related to the interaction between macrophages and biomaterial surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…5 c). A Study showed that when the polarized membrane is covering the bone defect area, the polarized materials created a favorable osteo-immunomodulatory environment, thus promoting osteogenic differentiation [ 37 ]. Our study shown the same results that the JEM(−) membrane effectively promoted the osteogenic differentiation of rBMSCs in vitro and the bone defect was filled with homogeneous and consecutive regenerated mature bone in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…5 c). A Study showed that when the polarized membrane is covering the bone defect area, the polarized materials created a favorable osteo-immunomodulatory environment, thus promoting osteogenic differentiation [ 37 ]. Our study shown the same results that the JEM(−) membrane effectively promoted the osteogenic differentiation of rBMSCs in vitro and the bone defect was filled with homogeneous and consecutive regenerated mature bone in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The extraction and induction of BMDMs was performed as previously described (Z. Y. Wang et al., 2021). Briefly, cells were flushed out of the femurs of C57BL/6 mice, treated with ice cold red blood cell lysate buffer (Boster) for 3 min, centrifuged, the supernatant discarded, and then resuspended in α medium (Gibco) containing 10% fetal bovine serum (CellMax), 1% antibiotic solution (10,000 units per mL penicillin and 10,000 μg/mL streptomycin, Gibco), and 30 ng/ml M‐CSF (R&D Systems) and cultured at 37°C (5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 98 ] Wang et al. [ 99 ] designed several charged poly(vinylidene fluoride‐trifluoroethylene) coating materials with different potential strengths to study the polarization behavior of mouse BMDMs. The charged surface not only upregulated the polarization behavior of macrophages, but also guided the polarization phenotype.…”
Section: Biomaterials Modulate Macrophage Polarization To Promote Bon...mentioning
confidence: 99%
“…The positively charged GO-PEI complexes exhibited higher intracellular delivery efficiency, whereas the negatively charged counterparts showed an enhanced immune inflammatory response in macrophages. [98] Wang et al [99] designed several charged poly(vinylidene fluoride-trifluoroethylene) coating materials with different potential strengths to study the polarization behavior of mouse BMDMs. The charged surface not only upregulated the polarization behavior of macrophages, but also guided the polarization phenotype.…”
Section: Surface Chargementioning
confidence: 99%